Pengujian Fungsional Aplikasi Penjualan Bahan Material Metode Black Box Testing - Reyven Ferdo Erlangga; Ade Irawan; Masuhan; Arief Saifudin (Shofanah Media Berkah, 2023)
Software testing is often interpreted as testing software or applications that are developed and do not have other parts in them. But in fact, software testing or application testing carried out by a software tester has other parts besides the tests being carried out. This section discusses testing with black box testing. The equivalence partitioning technique is used here for selection, and it is only used to test whether there are errors in the following aspects: system function, interface, data structure or data access, performance, and initialization. The number of forms tested is 3, which are the registration form, transaction form, and sales report. Each form is tested by entering some common input data. The research results show that in the application of material sales, software testing adopts the black box testing method and the equivalence partitioning technique. However, there is still a form where the output results are not as expected in the design due to errors. Errors that may occur due to wrong lines of code (syntax) Therefore, it is necessary to update the grammar to fix the error.